Implementación de un modelo sostenible de energía renovable a partir de materia orgánica en la finca Las Brisas, ubicada en el municipio de Puerto Rico (Meta) (2020)
This document proposes the owner of the case study, Finca Las Brisas, a self-sustainable solution that mitigates the negative impact of the disposal of organic waste in the open air, in such a way as to allow observe an economic benefit through biodigester technology. This with the in order to offer the entire community of Puerto Rico (Meta), a business model profitable and environmentally friendly in the Orinoquia region. Also, exposes the so-called energy transition as a global need that every time it worsens and, on the other hand, a problem with which the new generations. It is a material rich in renewable energy knowledge. Initially the frame reference exposes all those technologies that are at the forefront, as well as its fundamental principles. Through an analytical tool, contextualize issues of benefits and barriers regarding the implementation of renewable energy as a business model. Later they will be able to identify the importance of the primary sector, agriculture, in a cyclical economy and the impact that has generated the technification and entry of foreign competition in the production of the land. Finally, a complete portfolio of an overview of biodigester technology, as well as a brief cost-benefit analysis of a project of this complexity.